ALTERNATIF PEMECAHAN MASALAH KETERLAMBATANPENYELESAIAN PROYEK (STUDI KASUS PEMBANGUNAN GEDUNG PUSKESMAS LAREN KABUPATEN LAMONGAN) - Fridha Guivanny Putri; Rio Rahma Dana (Litbang Pemas - Universitas Islam Lamongan, 2018)
The successfulness of executing the construction projects right on time is one of the most important goals both for the owners and contractors. In general, each construction project has a specific implementation plan and schedule of implementation. It contains some important things, for example when the project should begin, when it should be completed, and how to provide the resources. As in the development project of Public Health Center building in LarenDistrict, Lamongan Regency in 2016 which has been delayed up to six weeks, causing inaccuracy between the planningschedule anddevelopment implementation. This research aims to be used as an evaluation to get the fastest acceleration time by using cut and crashing method. From the data obtained fromthe time schedule, cost estimate plan (RAB),wage price analysis, and project materials,the next step is making the job network and determining the critical pathfor cut and crash method. The results of the study show that the project acceleration can be done up to 82 days or 7 days faster than the normal day, that is 89 days with acceleration cost of Rp. 347.935.000,00 or increased from the normal cost of Rp. 345.390.000,00. The percentage of the selected acceleration time ratio is approximately 6.02% faster than the normal time, while for the acceleration cost is approximately 0.68% greater than the normal cost. Therefore, with this research, the work actually can be completed on December 13, 2016.